Towards User-Centric Transport in Europe Challenges, Solutions and Collaborations - Müller, Beate; Meyer, Gereon; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
In order to build a sustainable transport system for people and goods that meets the needs of all users, a truly integrated and seamless approach is needed, and the full potential of transformative technologies has to be exploited. This can only be achieved if user-centeredness, cross-modality and technology transfer become the paradigm of shaping future transport. Mobility4EU is a project funded by the European Commission that focusses on these topics and is working on delivering an action plan towards a user-centric and cross-modal European transport system in 2030. The authors of this contributed volume are dedicated scholars and practitioners connected to Mobility4EU either as partners or external contributors. Their contributions focus on understanding user needs and report on technologies and approaches that support the tailoring of a user-centered cross-modal transport system for passengers and freight on long distances and in the urban context.
Setting the scene - towards a vision for user-centric integrated and sustainable transport in 2030 -- Making transport accessible for all -- Improving urban mobility -- User-centric, sustainable and secure freight services -- Personalised and seamless services in passenger transport.
Keywords: Transportation engineering; Traffic engineering; Automobile industry and trade; Transportation Technology and Traffic Engineering; Automotive Industry